Interactions between centralized and decentralized water systems in urban context: A review. (30th June 2015) - Arora, Meenakshi; Malano, Hector; Davidson, Brian; Nelson, Rebecca; George, Biju
Abstract : This study presents a comprehensive review of the literature on implementation of various decentralized water systems along with centralized systems. The review highlights the benefits provided by these systems as well as various challenges posed associated with them. There are complex interactions involved within the water systems in an urban setting that are multidimensional and span over various aspects of water availability, quality, energy use, environmental, legal, economic, and social sectors. Although there are many economic, environmental, and social benefits associated with decentralized systems, there are some hidden challenges that are generally overlooked by planners and managers; these include the spatial integration of such systems, their energy intensity, social, economic, and environmental viability of these systems. Decisions to implement decentralized water systems require decision makers to consider economic, social, and environmental dimensions conjointly through an appropriate multicriteria decision analysis to select the hybrid water supply combination optimal for the given circumstances. The existing studies and tools are unable to address these factors using an integrated approach. So a holistic framework to evaluate and compare various water supply options in terms of energy use, social, economic, and environmental impacts is required to assess such systems in comprehensive manner. WIREs Water 2015, 2:623–634. doi: 10.1002/wat2.1099 This article is categorized under: Engineering Water > Planning Water Engineering Water > Sustainable Engineering of Water